Gelsemium elegans cyclic peptide induces human cervical carcinoma cells apoptosis through intrinsic and extrinsic pathways. (8th April 2022) - Liu, Jia; Liu, Fangting; Liu, Pingping; Xu, Hai; Tang, Longguo; Han, Xiuxia; Zheng, Man; Ren, Yuebing
Abstract : Four novel Gelsemium elegans cyclic peptides (GEPs) were isolated in an antihuman cervical carcinoma activity tracking method, and their amino acid sequences were identified. The GEP‐1 cyclic‐(Trp‐Leu‐His‐Val)‐peptide inhibited HeLa cell proliferation in a dose‐ and time‐dependent manner. GEP‐1 induced intracellular reactive oxygen species (ROS) overproduction and induced HeLa cells apoptosis in a caspase‐dependent manner. GEP‐1 also induced collapse of the mitochondrial membrane potential and promoted the mitochondrial release of cytochrome c (cyt c), apoptosis‐inducing factor (AIF), and endonuclease G (Endo G) in HeLa cells. Furthermore, GEP‐1 triggered the extrinsic death receptor‐dependent pathway, which was characterized by activating Fas and FADD. Notably, GEP‐1 is a potential antihuman cervical carcinoma peptide. Abstract : The GEP‐1 cyclic‐(Trp‐Leu‐His‐Val)‐peptide inhibits HeLa cell proliferation in a dose‐ and time‐dependent manner and induces intracellular reactive oxygen species (ROS) overproduction. It induces HeLa cell apoptosis by activating the death receptor‐mediated and intrinsic mitochondrion‐dependent pathways.